Laccase Production and Differential Transcription of Laccase Genes in Cerrena sp. in Response to Metal Ions, Aromatic Compounds, and Nutrients - Yang, Jie; Wang, Guozeng; Ng, Tzi Bun; Lin, Juan; Ye, Xiuyun (Frontiers in Microbiology, 2016)
Laccases can oxidize a wide range of aromatic compounds and are industrially valuable. Laccases often exist in gene families and may differ from each other in expression and function. Quantitative real-time polymerase chain reaction (qPCR) was used for transcription profiling of eight laccase genes in Cerrena sp. strain HYB07 with validated reference genes. A high laccase activity of 280.0 U/mL was obtained after submerged fermentation for 5 d. Laccase production and laccase gene transcription at different fermentation stages and in response to various environmental cues were revealed. HYB07 laccase activity correlated with transcription levels of its predominantly expressed laccase gene, Lac7. Cu2+ ions were indispensible for efficient laccase production by HYB07, mainly through Lac7 transcription induction, and no aromatic compounds were needed. HYB07 laccase synthesis and biomass accumulation were highest with non-limiting carbon and nitrogen. Glycerol and inorganic nitrogen sources adversely impacted Lac7 transcription, laccase yields and fungal growth. The present study would further our understanding of transcription regulation of laccase genes, which may in turn facilitate laccase production as well as elucidation of their physiological roles.